Penatalaksanaan Acne Vulgaris - Siratul Wahyuni; Mohamad Mimbar Topik (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2023)
Acne vulgaris is an androgen-dependent disorder of Pilosebaceous follicles (hair follicles and attached sebaceous glands). The areas of the body with the highest density of pilosebaceous follicles are the face, neck, upper chest, shoulders and back. Acne vulgaris is one of the most common skin disorders to be treated by a dermatologist, mainly affecting teenagers, although it may be present at any age. Acne Vulgaris by definition is a multifactorial chronic inflammatory disease of the Pilosebaceous unit. The various clinical presentations include seborrhoea, comedones, erythematous papules and pustules, less commonly nodules, deep pustules or pseudocysts, and primary scarring to name a few. Acne Vulgaris has four main pathogenetic mechanisms - increased sebum production, follicular hyperkeratinization, Propionibacterium acne (P.acne) colonization, and inflammatory products. In recent years, due to a better understanding of the pathogenesis of Acne Vulgaris, new therapeutic modalities are being designed. The availability of new treatment options to complement the existing armamentarium should help achieve successful therapy of more Acne Vulgaris patients, ensuring improved tolerability and meeting patient expectations. Successful management of Acne Vulgaris requires careful selection of anti-Acne Vulgaris agents according to the clinical presentation and individual patient needs.